Design of network topology based on delay-cost sink tree. (1st January 2013) - Dasgupta, Mou; Biswas, G.P.; Bhar, Chandan
The design of network topology is a challenging task and in this paper, a delay-cost sink-tree-based approach has been presented for its efficient design. Four delay costs like network-load delay cost, link-bandwidth delay cost, link delay cost and processing delay cost have been identified and defined, and a multi-objective delay-cost model based on these four delays has been developed to represent the total data transmission delay of a given data network. Now based on the delay model, a sink-tree for each and every node of the network is developed, which are then analysed and integrated together to design the final topology such that the links, whose contributions are not significant, are not considered. A network reliability check-point is kept so that on removal of the link(s) from the existing network, the reliability is decreased minimally. Two numerical examples, one of which is an existing network connecting ten major cities of China, are given to elaborate the proposed technique of designing network topology.